Manual on Laboratory Testing of Fishery Products - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
This manual provides practical guidelines for laboratory managers and analysts, regarding the requirements for development of a range of tests for assessing the food safety of fishery products. The manual sets out the testing methods for fishery products, to be conducted by testing laboratories engaged in assessing chemical and microbiological food safety parameters applicable to fishery products. It will be especially useful in instructing Competent Authorities (CAs) and their designated laboratories on how to develop a comprehensive testing capacity for certification of fishery products for international trade.